TMIC-53. DEVELOPMENT OF A GEO-TAGGED TUMOR SAMPLE REGISTRY; LINKAGE OF TUMOR SAMPLE LOCATION TO IMAGING CHARACTERISTICS. (14th November 2022) - Lynes, John; Rubino, Sebastian; Etame, Arnold; Liu, James; Beer-Furlan, Andre; Tran, Nam; Ruiz, Alexia; Macaulay, Rob; Vogelbaum, Michael
Abstract: Background: Significant intra- and inter-heterogeneity exists in gliomas. This provides clinical, radiological, diagnostic, and treatment challenges. To date, there have been few efforts to comprehensively catalog information obtained in the operating room that spatially links neuro-navigation localization to imaging characteristics, gross intraoperative visual findings, and pathological/molecular features. The value of this spatial localization is probably greatest in high grade gliomas, which have been demonstrated to have intra-tumoral histological and genetic/epigenetic heterogeneity. METHODS: An IRB-approved institutional registry of patients undergoing clinically-indicated surgery with use of an image-guidance system (IGS) was launched in November 2019 and as of June 1, 2022 includes nearly 500 patients, of which 243 were diagnosed with gliomas. Intraoperatively, locations within the gross tumor or tumor-infiltrated brain were sampled at each surgeon's discretion, and each sample was linked to their precise location with the IGS system ("geo-tagged"). The registry includes information regarding surgeon; anesthesia technique; use of intraoperative tumor fluorescence; tumor location and volume; pathologic diagnosis and molecular features, and sample number. RESULTS: Of 243 gliomas, 26 were low grade and 217 were high grade with 174 being glioblastoma. For enhancing tumors, volume of enhancement ranged from 0.31 to 127.0 cm3 with an average of 22.9 cm3. Tumors were widely distributed throughout the cerebrum with 133 left-sided tumors, 110 right-sided and 32 spanning multiple lobes or deep subcortical structures including the brainstem. 51% of surgeries were under awake anesthesia, and 40% were performed using fluorescence guidance. The average number of navigation image-linked samples collected per tumor was 3.67; 3.48 in low grade gliomas, and 3.69 in high grade gliomas. Samples are archived in frozen and/or formalin-fixed, paraffin-embedded formats for future research. CONCLUSION: This registry provides the foundation for correlation of imaging, intraoperative findings, and pathology in brain tumors, and it will support detailed laboratory/translational investigations addressing tumor heterogeneity.